Diagnosis of early relapse in ovarian cancer using serum proteomic profiling - Gao, Jean (Henry Stewart Talks, 2007)
Surface-enhanced laser desorption/ionization time-of-flight (SELDI-TOF) mass spectrometry data, Use of Biomarkers to identify diverse early disease detection, Ovarian cancer relapse diagnosis, SVM-MB/RFE: Support Vector Machine- Markov Blanket/Recursive Feature Elimination to identify biomarkers for predicting the early recurrence of ovarian cancer by analyzing SELDI-TOF mass spectrometry data
Archived at 2018/10/28